2006
DOI: 10.1086/507635
|View full text |Cite
|
Sign up to set email alerts
|

Slower Rates of Clearance of Viral Load and Virus‐Containing Immune Complexes in Patients with Dengue Hemorrhagic Fever

Abstract: These findings indicate that slower rates of clearance of viral load and virus-containing immune complexes are associated with subsequent immune activation and contribute to the progression of DHF at this critical stage. Moreover, viral load on the day of defervescence can predict cases of DHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
145
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 41 publications
16
145
1
4
Order By: Relevance
“…Studies that use PCR as an indicator for dengue virus detection show that viremia is higher in DHF versus DF patients. [30][31][32][33] Although antibody-virus complexes and neutralized virus would impact viral biological assays such as viral isolation, they would not likely impact PCR readouts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that use PCR as an indicator for dengue virus detection show that viremia is higher in DHF versus DF patients. [30][31][32][33] Although antibody-virus complexes and neutralized virus would impact viral biological assays such as viral isolation, they would not likely impact PCR readouts.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Flaviviral infections, such as yellow fever, West Nile fever, and especially dengue fever, are among the most common arboviral infections worldwide, but the resulting symptoms are non-specific, leading to misdiagnosis. [14][15][16] For example, chikungunya fever, caused by the alphavirus chikungunya virus, is an emerging infectious disease in endemic and non-endemic regions and can be misdiagnosed as dengue fever, which is largely sympatric in the Old World. [16][17][18][19][20][21] Because the clinical presentation of arboviral disease is often non-specific, reliance on diagnostic testing becomes necessary for accurate differentiation.…”
mentioning
confidence: 99%
“…In addition, significant cross reactivity between DENV serotypes was shown in CD8(+) T-cells after a naturally acquired primary infection with differential T-cell receptor signalling after stimulation with homologous and heterologous peptides (Friberg et al 2011). DENV entry is facilitated by the phagocytosis of immune complexes via Fc receptors on monocytes (Daughaday et al 1981) and studies of immune responses have reported circulating immune complexes and complement activation during the fever-to-defervescence period in which haemorrhage, plasma leakage and/or circulatory failure occur in patients with DHF and/or OSS (Ruangjirachuporn et al 1979, Wang et al 2006.…”
mentioning
confidence: 99%